2019
DOI: 10.3390/su11092500
|View full text |Cite
|
Sign up to set email alerts
|

Density of Biogas Power Plants as An Indicator of Bioenergy Generated Transformation of Agricultural Landscapes

Abstract: The increasing use of biogas, produced from energy crops like silage maize, is supposed to noticeably change the structures and patterns of agricultural landscapes in Europe. The main objective of our study is to quantify this assumed impact of intensive biogas production with the example of an agrarian landscape in Northern Germany. Therefore, we used three different datasets; Corine Land Cover (CLC), local agricultural statistics (Agrar-Struktur-Erhebung, ASE), and data on biogas power plants. Via kernel den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
6
11
0
Order By: Relevance
“…Therefore, biomass was generally obtained from the immediate vicinity of a biogas plant. This finding was confirmed by the research of Csikos et al [29], who found that biogas plants were concentrated in areas where energy crops were largely cultivated. In addition, it has been found that areas with higher biogas technical potential had biogas plants with higher capacities [25].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, biomass was generally obtained from the immediate vicinity of a biogas plant. This finding was confirmed by the research of Csikos et al [29], who found that biogas plants were concentrated in areas where energy crops were largely cultivated. In addition, it has been found that areas with higher biogas technical potential had biogas plants with higher capacities [25].…”
supporting
confidence: 71%
“…Considering CLC changed-maps only report arable land change as one land use type, which limits the analysis for silage maize area changes during various EEGs, the detailed agricultural crops area was derived from regional crop statistic record to facilitate evaluation. To relate dynamic changes in the agricultural landscape to biogas plant installed capacity density, we adopted the approach from Csikos et al[29]. Three impact zones (A, B and C), representing different density categories (low, medium and high) of the installed capacity (kWel./km 2 ) of biogas plants, were delineated using the Kernel Density tool within ArcGIS 10.7 software.…”
mentioning
confidence: 99%
“…The silage maize and winter rapes are the dominant land-use types of the energy landscapes. Based on Csikos et al [13], there is a significant positive correlation between the capacity of the biogas power plants and the area of silage maize and rape.…”
Section: Discussionmentioning
confidence: 99%
“…Model I.1 was used to explore the impact of environmental, social and economic factors on the decision to adopt biogas production. Model I.1 was constructed as follows: To spatially study the impacts of environmental, social and economic factors on biogas plant production density, we adopted the impact zone analysis approach of Csikos et al [75]. Using the spatial join function of the ArcGIS 10.7 software, the data used in the empirical analysis on each investigated environmental, social and economic factor except for PPAP was assigned to the corresponding county to create the factor map.…”
Section: Model Specificationmentioning
confidence: 99%